Centrifugal bimetal cylinders of turn-screw conical extruders - Гладченко, А.Н.; Шевеля, В.В.; Зверлин, В.Г. (Problems of Tribology, 2014)
On the basis of technology of centrifugal induction naplavki the complex of works, directed on creation of effective technology, allowing to equip turn-screw conical extruders corps with inflicted by a centrifugal method the conical openings was conducted